PROYECTO DE FACTIBILIDAD PARA LA PRODUCCIÓN Y COMERCIALIZACIÓN DE LECHE DE ARROZ EN EL CANTÓN MACARÁ, PROVINCIA DE LOJA. - Arrobo Piedra, Yamileth Maria (2024)
The Curricular Integration Work was developed within the framework of the requirements of an investment project in the Macará canton, for which a “Feasibility Project for the Production and Commercialization of Rice Milk in the Macará Canton, Province of Loja” has been proposed. A market study was conducted that determined an unsatisfied demand of 251,857 liters. For this purpose, a survey was applied to 357 families, which were distributed in each of the parishes of the canton. In the Technical Study, the macro and micro location is established, identifying the optimal location of the project through a matrix of location factors. The selected location is in the Eloy Alfaro Parish, San Sebastián, El Ejército avenue and Mayaycu street in the Macará canton, province of Loja. It was established that the company will be constituted as a natural person not required to keep accounting records, with a structural organization chart for each of the company's jobs. In the Financial Study, a total investment of $63,535.55 was determined, financed by 21.30% equity (equivalent to $13,535.55) and the remaining 78.70% ($50,000.00) through a loan from the JEP Cooperative at an interest rate of 10.70% and a term of 4 years. In the Financial Evaluation, the following indicators were determined: Net Present Value of $347,337.37; Internal Rate of Return of 174.95%, which is higher than the cost of capital; Benefit-Cost Ratio of $1.07 for each dollar invested; a Capital Recovery Period of 8 months and 26 days; and, the Sensitivity Analysis showed that the project supports an increase in costs up to 69.86% and a decrease in income of 33.68%. Based on the results, it is concluded that the project is viable for execution.